The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0cc05118g
|View full text |Cite
|
Sign up to set email alerts
|

A straightforward synthesis of a new family of molecules: 2,5,8-trialkoxyheptazines. Application to photoredox catalyzed transformations

Abstract: We have prepared several 2,5,8-trialkoxyheptazines starting from the soluble precursor 2,5,8-tris(3,5-diethylpyrazolyl)-heptazine. We present their syntheses along with their promising spectroscopic and electrochemical properties, which demonstrate large band gaps and high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Generally, s -heptazines bearing heteroatomic substituents are colorless (white) or very slightly yellow with most of them absorbing above 300 nm, while some molecules display a tiny absorption tail or shoulder in the visible range, likely due to a charge transfer band of a very low intensity. ,, , These compounds all exhibit fluorescence, stemming from the same low-intensity band, with a broad emission going from violet (amino derivatives) through bluish white (TPDH) to orange-red (thiol derivatives in the solid state). Fluorescence quantum yields (QYs) are rarely given , but are usually low to average (10–20%) while exhibiting long lifetimes, , reminiscent of thermally activated delayed fluorescence (TADF). In some occurrences, the emission color and QYs are different in the solid state than in solution, which suggests that aggregated induced emission (AIE) might also be encountered although no proof has yet been given.…”
Section: Physical Chemistry Of S-heptazinesmentioning
confidence: 94%
See 2 more Smart Citations
“…Generally, s -heptazines bearing heteroatomic substituents are colorless (white) or very slightly yellow with most of them absorbing above 300 nm, while some molecules display a tiny absorption tail or shoulder in the visible range, likely due to a charge transfer band of a very low intensity. ,, , These compounds all exhibit fluorescence, stemming from the same low-intensity band, with a broad emission going from violet (amino derivatives) through bluish white (TPDH) to orange-red (thiol derivatives in the solid state). Fluorescence quantum yields (QYs) are rarely given , but are usually low to average (10–20%) while exhibiting long lifetimes, , reminiscent of thermally activated delayed fluorescence (TADF). In some occurrences, the emission color and QYs are different in the solid state than in solution, which suggests that aggregated induced emission (AIE) might also be encountered although no proof has yet been given.…”
Section: Physical Chemistry Of S-heptazinesmentioning
confidence: 94%
“…This may seem as an unpassable hurdle, but we managed to overcome it, using the new process of mechanochemistry, more precisely ball-milling. , Indeed, crushing the crude, unpurified tris­(hydrazino)- s -heptazine for only about 15 min with a moderate excess of the pure diketone and an acidic catalyst yielded TDPH ( 72 ) with a 30–40% yield on a few grams’ scale (Scheme ). Audebert’s group was able in the same publication to demonstrate the exchange of the pyrazolyl groups by mild nucleophiles, such as thiols and amines (Scheme ), and very recently alcohols …”
Section: Synthetic Approaches For Molecular S-heptazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 More recently, new derivatives of Hz were synthesized [4][5][6] and their use as emitters in organic light-emitting diodes (OLEDs) [7][8][9] or as photoredox catalysts were explored. 10,11 A comprehensive up-to-date account of the literature on molecular (monomeric) Hz and derivatives thereof can be found in Ref. 12 The polymer melon, also referred to as graphitic carbon nitride (g-C3N4), has found vast attention as a metal-free and photochemically highly stable photocatalyst for hydrogen evolution from water with sacrificial reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Correlated wave function theories suggested that S 1 of heptazine lies 0.2-0.3 eV below T 1 , though S 1 is a 'dark' state, meaning that the electronic transition to the ground state (S 0 ) is dipole-forbidden and the oscillator strength (f) is zero in the D 3h symmetry point group. Interestingly, the heptazine core is shared by several synthesised molecules that exhibit intense TADF with positive DE ST [21][22][23][24] . We thus hypothesized that appropriate chemical substitutions would lead to heptazine analogues with negative DE ST and su cient f for intense uorescence.…”
mentioning
confidence: 99%